2016
DOI: 10.1136/bmjopen-2015-009351
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective morphometric study of the suitability of renal arteries for renal denervation according to the Symplicity HTN2 trial criteria

Abstract: ObjectiveThe aim of this study was to describe the renal arteries of humans in vivo, as precisely as possible, and to formulate an expected value for the exclusion of renal denervation due to the anatomical situation based on the criteria of the Symplicity HTN trials.Design and settingIn a retrospective cohort study, the renal arteries of 126 patients (57 women, 69 men, mean age 60±17.2 years (CI 57.7 to 63.6)) were segmented semiautomatically from high-contrast CT angiographies.ResultsAmong the 300 renal arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
4
3
1
Order By: Relevance
“…The liver forces the right kidney to be lower, more medially displaced and smaller than the left. The renal arteries arise from the lateral aspect of the aorta below the level of the superior mesenteric artery and because the right artery passes posterior to the inferior vena cava it is longer than the left, and indeed our findings confirm these observations [14,22]. We add however also what these studies did not show [22], that the left main renal artery is of larger diameter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The liver forces the right kidney to be lower, more medially displaced and smaller than the left. The renal arteries arise from the lateral aspect of the aorta below the level of the superior mesenteric artery and because the right artery passes posterior to the inferior vena cava it is longer than the left, and indeed our findings confirm these observations [14,22]. We add however also what these studies did not show [22], that the left main renal artery is of larger diameter.…”
Section: Discussionsupporting
confidence: 90%
“…The renal arteries arise from the lateral aspect of the aorta below the level of the superior mesenteric artery and because the right artery passes posterior to the inferior vena cava it is longer than the left, and indeed our findings confirm these observations [14,22]. We add however also what these studies did not show [22], that the left main renal artery is of larger diameter. Our data also suggest that accessory renal arteries are associated with longer main renal arteries, in contrast to previous studies that described solitary renal arteries as longer [14].…”
Section: Discussionsupporting
confidence: 90%
“…It is essential for the radiologists and surgeons to have background knowledge of normal range of renal artery measurements and variation in measurementsin a specific population as this can affect complex and expertise required procedure. 23 , 24 In our study a significant difference was observed between mean diameter of right and left main renal arteries. Mean diameter of right renal artery was found to be smaller than mean diameter of left renal artery.…”
Section: Discussionsupporting
confidence: 49%
“…Studies have shown great variability in the renal vasculature. In one clinical trial this resulted in nearly 50% of patients to be unsuitable for direct renal denervation therapy (Schönherr et al, 2016; Song et al, 2020). The varied results from the clinical trials, has led researchers to investigate the anatomy of the surrounding area as well as the potential of blocking the aorticorenal ganglion instead (Hori et al, 2021; Reetu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%